Multi-configuration Stiffened Panels under Compressive Load: Part 1 – Theoretical Analysis - Ramly, Ramzyzan; Kuntjoro, Wahyu; Radzi Abdul Ghani, Amir; Effendy Mohd Nasir, Rizal; Muhammad, Zulkifli (International Journal of Engineering and Technology, 2018)
Stiffened panels are the structure used in the aircraft wing skin panels. Stiffened panels are often critical in compression load due to its thin structural configuration. This paper analyzes the critical loads of a multi configuration stiffened panels under axial compressive loading. The study comprised three main sections; theoretical analysis, numerical analysis and experimental analysis. The present paper deals only with the theoretical analysis. This first part of analysis is very important since the results will be the main input parameter for the subsequent numerical and experimental analysis. The analysis was done on the buckling properties of the panels. Four panel configurations were investigated. Results showed that even though the stiffened panels have the same cross-sectional area, their critical loads were not identical.Â Â Â